What would most help improve the quality of life of older family carers of people with dementia? A qualitative study of carers’ views - Oliveira, D.; Sousa, L.; Aubeeluck, Aimee (SAGE, 2018)
Older family carers of people with dementia provide a substantial amount of care for people with dementia in the UK. Caregiving can be stressful and burdensome for these individuals, who are also experiencing psychological and physical changes resulting from their own ageing process. However, little is known about what impacts their quality of life, how this can be improved and what we should prioritise. This brief report asks one simple question to older family carers of people living with dementia – “What would most help improve your quality of life as a carer?” Qualitative data was collected from 150 carers who completed an anonymous paper survey during the development and validation of a quality of life tool for use with this population (DQoL-OC). Participants were individuals aged 60 and over and were providing care for a family member with dementia at home in the UK. Carers were recruited from a variety of voluntary organizations, community-based carers’ groups, health services and via online forums. A thematic approach was used to analyse the carers’ comments and three main overarching themes were identified. The quality of life of older family carers can be enhanced by having more time away from caregiving, accessing health and social services that are dementia friendly and by having economic support. Future care, policies and research should aim to address these key areas in order to promote better quality of life for older carers of people with dementia. Further implications for practice, policy and research are discussed.